The causes of the voluntary withdrawal of African states from their sub-regional community - Zainou Tangui, Ibrahim Zeidane; Tenkoul, Abderrahman (Frontiers in Political Science, 2025)
Africa has seen several voluntary withdrawals from its sub-regional community, one of the most striking and surprising of which was that Burkina Faso, Mali, and Niger jointly withdrew from the Economic Community of West African States in 2024. An African sub-regional community is an organization bringing together several African states to collaborate, cooperate, and find solutions together to aspire to desirable development for both their states and their populations. The aim of this article, then, is to highlight the causes of the voluntary withdrawal of African states from their sub-regional community in Africa. Because these causes are diverse, and because previous research has not highlighted them all, having dealt only with the consequences of the withdrawal of these States from their sub-regional community, and because of their lack of public awareness. A specific study on the causes of voluntary withdrawal of African states from their sub-regional community is also lacking. Several qualitative research approaches (triangular approach) have been used to address the subject of the causes relating to the voluntary withdrawal of African States from their sub-regional community. Among these causes are: the will of the people and the choice of African states resigning from non-compliance with the re-establishment of constitutional order, rules and decisions of the sub-regional community; the sub-regional community sanctions against resigning African states and the lack of credibility of the sub-regional community according to resigning African states; the sense of self-sufficiency and responsibility of African states resigning from the sub-regional community. Finally, the article proposes ideas that could help African sub-regional community to prevent and avoid the deliberate withdrawal of some of their member states, and to spare the African Continent from being so divided that states turn on each other.